Tunable single-photon nonreciprocal scattering and targeted router in a giant atom-waveguide system with chiral couplings. (1st March 2023) - Sun, Xue-Jian; Liu, Wen-Xiao; Chen, Hao; Li, Hong-Rong
Abstract: We investigate the single-photon scattering properties of a driven three-level giant atom chirally coupled to two waveguides simultaneously in both the Markovian and the non-Markovian regimes. It is shown that under the Markovian limit, the chiral photon-atom interactions enable nonreciprocal scattering in a single waveguide and targeted photon routing with a probability of 100% in two waveguides, while the presence of the driving field and the giant atom structure introduce a more tunable parameter to manipulate the single-photon scattering behaviors. We also examine how the non-reciprocity and routing capability are influenced by the imperfect chirality and the atomic dissipation. In the non-Markovian regime, we show that the scattering behaviors are more complicated. The non-Markovicity induced non-reciprocity and photon routing are demonstrated in this paper. We believe that those results have potential applications in quantum network engineering.